Effect of oral creatine supplementation on jumping and running performance - Bosco, C.; Tihanyi, J.; Pucspk, J.; Kovacs, I.; Gabossy, A.; Colli, R.; Pulvirenti, G.; Tranquilli, C.; Foti, C.; Viru, M.; Viru, A. (International Journal of Sports Medicine, 1997)
The study was designed to investigate the effect of creatine monohydrate ingestion (20 g daily for 5 days) on performance in 45 s maximal continuous jumping and in all-out treadmill running at 20 km x h(-1), (inclination 5 degrees, duration approximately 60s). The participants were qualified sprinters and jumpers. The effect of creatine was compared with placebo in a double-blind design. Creatine (Cr) supplementation led to a significant enhancement of performance capacity in the jumping test by 7% during the first 15 s and by 12% during the second 15 s of the exercise. The positive effect of Cr supplementation was not observed in the last third of the continuous jumping exercise, when the contribution of anaerobic metabolism was decreasing. The time of intensive running up to exhaustion improved by 13%. The results show that Cr supplementation helps to prolong the time during which the maximal rate of power output could be maintained.